Uber die Stabilitat der diastereomeren Aloine A und B sowie ihr Haupt- Zersetzungs-Produkt 4-Hydroxyaloin - Graf, E.; Alexa, M.
The two diastereomeric aloins A and B are iil pure state fairly stable. Their stability against air, solvents, pH influence, peroxide, heat, and light is described. In presence of alkali or of impurities they are converted into one another and quickly decomposed. The main decomposition product is 4-hydroxyaloin, as shown by analytic and spectroscopic data.
Keywords: ALOE; LILIACEAE; ALOIN; DIASTEREOMERS; 4-HYDROXYALOIN; STABILITY; FRAGMENTATION